Concept of Swarnaprashana As Jatakarma Samskara (Birth ritual) - Swami, Monika; Swami, Kanchan; Rao, K Shankar (International Research Journal of Ayurveda & Yoga, 2021)
Introduction- Swarnaprashana formulation is a unique method of administration of gold contain medicament to neonate. Literal meaning of Prashana is to lick i.e application of medicament on the tongue. The use of Gold internally in children through oral route is first available in the Kashyapa Samhita with the name of Swarna Prashana. Gold licking is also mentioned by Sushruta, Vagbhatta and other Acharyas immediately after the birth as a part of Jatkarma Samskara (birth ritual). Ancient Acharya of Ayurveda has given more thrust to the development of body’s defense system against diseases rather than focusing the disease. As far as pediatric cases are concerned Acharya had taken special care to boost up the immune system of the infant from the time of birth itself. The purpose of Swarna-Prashan is same as of modern vaccination to prevent diseases by building immunity. It also benefits in a proper brain development, improves memory, intelligence, verbal and cognitive functions of the brain. All the above said benefits are indicating the enhancement of all favorable factors required for proper growth and development of a child.